2013
DOI: 10.1111/mmi.12375
|View full text |Cite
|
Sign up to set email alerts
|

Regulated DNA rearrangement during sporulation in Bacillus weihenstephanensisKBAB4

Abstract: SummaryTemperate phages can integrate their genomes into a specific region of a host chromosome to produce lysogens (prophage). During genome insertion, prophages may interrupt the gene coding sequence. In Bacillus subtilis, the sigma factor gene sigK is interrupted by a 48 kb prophage-like element. sigK is a composite coding sequence from two partial genes during sporulation. For over two decades, however, no further examples of DNA element-mediated gene reconstitution other than sigK have been identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
(61 reference statements)
0
32
0
Order By: Relevance
“…One plausible reason why all of the sporulation gene-intervening elements possess the LSR-encoding gene (e.g. spoIVCA in B. subtilis skin (1518), ssrA in B. weihenstephanensis vfbin (20), Geoth_3268 in Geobacillus thermoglucosidasius (20)) may be to carry out precise gene rearrangements in a similar manner to SprA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible reason why all of the sporulation gene-intervening elements possess the LSR-encoding gene (e.g. spoIVCA in B. subtilis skin (1518), ssrA in B. weihenstephanensis vfbin (20), Geoth_3268 in Geobacillus thermoglucosidasius (20)) may be to carry out precise gene rearrangements in a similar manner to SprA.…”
Section: Resultsmentioning
confidence: 99%
“…During sporulation, skin is excised from the chromosome to combine the ORFs in frame (1416,18). Many other examples of sporulation-specific gene rearrangement, in addition to sigK , suggest that this phenomenon is wide-spread and common in spore-forming bacteria (20). In a previous study, we found that SPβ, an ‘active’ prophage, generates a gene rearrangement of spsM ( s pore p olysaccharide s ynthesis M) in B. subtilis strain 168 (21).…”
Section: Introductionmentioning
confidence: 99%
“…On shorter time scales, even single rearrangement events such as duplications, amplifications, inversions, deletions, and translocations can have profound effects on organismal phenotypes, typically by altering gene regulation or disrupting genes. In bacteria, some genome rearrangements have led to traits important for virulence (6), and rearrangements are sometimes even developmentally regulated (7). …”
Section: Introductionmentioning
confidence: 99%
“…For heterocyst-forming cyanobacteria, these developmentally regulated genomic DNA deletions exclusively occurred in developing or mature heterocysts 22, 37 , but have not yet been observed in vegetative cells. Similarly, during sporulation, regulated genomic DNA deletions (a 42.1-kb spoVFB element and a 48-kb sigK element) occurred exclusively in mother cells of Bacillus weihenstephanensis KBAB4 and B. subtilis , but were not seen in their forespores 21, 43, 44 . Interestingly, both the heterocysts and the mother cells are terminally differentiated, non-dividing cells, unable to produce a next generation and eventually die.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both the heterocysts and the mother cells are terminally differentiated, non-dividing cells, unable to produce a next generation and eventually die. Therefore, the genomic DNA continuity is preserved in vegetative cells in heterocyst-forming cyanobacteria and in spores of spore-forming Bacilli 43, 44 .…”
Section: Discussionmentioning
confidence: 99%